Extracellular matrix from decellularized mesenchymal stem cells improves cardiac gene expressions and oxidative resistance in cardiac C-kit cells - Ng, Wai Hoe; Ramasamy, Rajesh; Yong, Yoke Keong; Ngalim, Siti Hawa; Lim, Vuanghao; Shaharuddin, Bakiah; Tan, Jun Jie (Elsevier, 2019)
Objective Myocardial infarction remains the number one killer disease worldwide. Cellular therapy using cardiac c-kit cells (CCs) are capable of regenerating injured heart. Previous studies showed mesenchymal stem cell-derived (MSC) extracellular matrices can provide structural support and are capable of regulating stem cell functions and differentiation. This study aimed to evaluate the effects of human MSC-derived matrices for CC growth and differentiation.